Improving emotion regulation ability in autism: The Emotional Awareness and Skills Enhancement (EASE) program. (July 2019) - Conner, Caitlin M; White, Susan W; Beck, Kelly B; Golt, Josh; Smith, Isaac C; Mazefsky, Carla A
Emotion regulation impairments are common among individuals with autism spectrum disorder and are believed to often underlie commonly seen problems with aggression, depression, and anxiety. The Emotional Awareness and Skills Enhancement program was developed to reduce emotion regulation impairment and thereby improve behavioral disturbance, via mindfulness. Emotional Awareness and Skills Enhancement consists of a 16-week individual therapy treatment targeting emotion regulation impairments among individuals with autism spectrum disorder. We describe the conceptual framework and development of the program and present data on feasibility and preliminary efficacy from a pilot trial. The Emotional Awareness and Skills Enhancement manual was developed using a participatory action framework, based on emotion regulation research specific to autism spectrum disorder and input from individuals with autism spectrum disorder, therapists, and parents of children with autism spectrum disorder. Emotional Awareness and Skills Enhancement was piloted in a two-site open trial with 20 participants with autism spectrum disorder (12–17 years old, confirmed autism spectrum disorder diagnosis, IQ > 80).Outcome data support program feasibility and acceptability to participants, as well as significant improvement in emotion regulation impairments and related concerns.Findings offer preliminary support for both the feasibility and clinical effectiveness of the Emotional Awareness and Skills Enhancement program.